2017
DOI: 10.1590/1807-3107bor-2017.vol31.0067
|View full text |Cite
|
Sign up to set email alerts
|

Antibiotic therapy as an adjunct to scaling and root planing in smokers: a systematic review and meta-analysis

Abstract: The aim of this study was to perform a systematic review and meta-analysis to examine the effect of systemic antibiotics in the periodontal treatment of smokers. The selection criteria were as follows: controlled randomized clinical trials; studies published in English; studies with smoker patients diagnosed with chronic periodontitis; patients without systemic diseases; studies that used systemic antibiotic therapy associated with periodontal treatment; studies that presented results for the test and control … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
11
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 60 publications
4
11
0
2
Order By: Relevance
“…In line with the findings of the present work, other studies have shown that the use of an adjunctive therapy with MTZ or MTZ + AMX has clinical and microbiological treatment benefits in non-smoking patients with chronic periodontitis [2,[32][33][34] as well as in patients who smoke [22,30]. There is still no consensus on antibiotic protocol in smokers [35], although certain studies have used the combination of MTZ + AMX for a period of 7 [30] or 14 [22,25] days. Another study suggested that smokers may specifically benefit from being treated with a combination of MTZ + AMX in the non-surgical phase, and that this reduces the need for surgery [8].…”
Section: Discussionsupporting
confidence: 81%
“…In line with the findings of the present work, other studies have shown that the use of an adjunctive therapy with MTZ or MTZ + AMX has clinical and microbiological treatment benefits in non-smoking patients with chronic periodontitis [2,[32][33][34] as well as in patients who smoke [22,30]. There is still no consensus on antibiotic protocol in smokers [35], although certain studies have used the combination of MTZ + AMX for a period of 7 [30] or 14 [22,25] days. Another study suggested that smokers may specifically benefit from being treated with a combination of MTZ + AMX in the non-surgical phase, and that this reduces the need for surgery [8].…”
Section: Discussionsupporting
confidence: 81%
“…Residual pockets during SRP present similar challenges and additional therapeutic approaches to achieving periodontal health are required. To improve the results of mechanical debridement, antibiotics are widely used [ 3 , 4 ]. Limitations of drug resistance associated with the use of local and systemic medications have led to the popularity of antimicrobial photodynamic therapy (aPDT) in the management of chronic periodontitis.…”
Section: Introductionmentioning
confidence: 99%
“…The standard management of periodontal diseases focuses on infection control, detoxification of dental surfaces, regeneration of lost tissues, and plaque-control regimens via mechanical debridement (such as scaling and root planning (SRP)) [7]. Other therapeutic modalities, such as antiseptics and/or antibiotics, laser therapy, guided bone regeneration, and air-polishing, have also been proposed [811]. However, the outcomes of clinical treatment remain less than ideal.…”
Section: Introductionmentioning
confidence: 99%